Laparoscopic excision of abdominopelvic Ewing’s Sarcoma in a child: A case report - Bilal Qayyum; Sajid Ali; Tariq Latif (Journal of University Medical & Dental College, 2025)
Ewing sarcoma is a rare and aggressive neoplasm that primarily affects the bones and soft tissues of pediatric and adolescent patients. When located in the abdominopelvic region, it poses challenges for treatment due to its proximity to vital organs. We present a case of a 16-year-old male diagnosed with abdominopelvic Ewing sarcoma. He presented with abdominal pain and swelling extending from the pelvis to above the umbilical region. CT imaging revealed a large mass with both solid and cystic components originating from the pelvic area, with surrounding displacement. A core needle biopsy confirmed the diagnosis. Neo-adjuvant chemotherapy was initiated to reduce the tumor size. Post-treatment imaging revealed two masses, one in the pelvis and one in the peri-splenic area. Laparoscopic surgery successfully excised abdominopelvic Ewing’s Sarcoma. Histopathology showed clear resection margins and 60% necrosis. Adjuvant radiotherapy was given to minimize recurrence. This case demonstrates successful management using a multidisciplinary approach.